Evaluation of the Presence of Bacterial and Viral Agents in the Semen of Infertile Men: A Systematic and Meta-Analysis Review Study - Gholami, Mehrdad; Moosazadeh, Mahmood; Haghshenash, Mohammad Reza; Jafarpour, Hamed; Mousavi, Tahoora (Frontiers in Medicine, 2022)
Objectives: Bacterial and viral infections play a disruptive and hidden role in spermatogenesis and male fertility. A meta-analysis review study was performed to assess the potential role of viral and bacterial infections in male infertility. Methods: Relevant cross-sectional and/or case-control studies were found using online reviewing the national and international databases (Web of science, Pubmed, Scopus, Science Direct, Google scholar), and suitable studies were selected. The qualities of all papers were determined by a checklist. Heterogeneity assay amongst the primary studies was evaluated by Cochran's Q test and I2 index (significance level of 50%). The statistical analysis was done using the Comprehensive Stata ver. 14 package (StataCorp, College Station, TX, USA). Results: Seventy-two studies were included into this meta‐analysis. Publication bias was compared with the Egger's test and the impact of each research on the overall estimate was evaluated by sensitivity analysis. In 56 studies, the rate of bacterial infections in the semen of infertile men was 12% (95% confidence interval [CI]: 10–13). Also, in 26 case-control studies, the association of infertility in men with bacterial infections was evaluated. The results show that the odds ratio of infertility in men exposed to the bacterial infections is 3.31 times higher than non-infected (95% CI: 2.60-4.23). Besides, in 9 studies that examined the prevalence of HPV, HSV1, HSV2, HSV1-2 viruses in infertile men, the frequency of these viruses was 15% (CI 95%: 9-21). In 6 case-control studies, the association between HCMV, CMV and HPV viruses with male infertility was evaluated and the chance of male infertility being exposed to these viruses was 2.24 times higher than those without exposure to these viruses (CI 95%: 1.9-4.52). The results show that the ratio of chance of infertility in men exposed to bacteria was significantly higher than un-infected population. Conclusion: This meta-analysis showed that the presence of viral and bacterial infections is a risk factor and could impair male fertility potential. Also, our study supports the hypothesis that co-infections could play a key role in the impairment of sperm quality in the male population.